The Development and Challenges in Sports: A Case Study of the Indian Cricket - Singh, Jaswinder; Nanda, Inderpreet Kaur; Chaturvedi, Ravi; Dhingra, Sanchita (Advances in Social Sciences Research Journal, 2021)
Cricket is the most popular game at present not in only in India but also in the Indian Subcontinent. The controversies and the ups and downs of the willow game have been the subject of discussion by the cricket chroniclers and the lovers of the game in times gone by. The present study aims at examining the level of motivation among players, nature and role of cooperation from academic institutions such as the college or the university, from the family, need for a different academic course structure for players and fairness in the selection process. Using the information through a sample of 320 student cricketers, the role of the University of Delhi in nurturing the talent and producing some outstanding cricketers of national and international levels has been probed. Absence of trainers along with commensurate infrastructure seems to be the bane in developing top cricketers in the Colleges and the Universities. Forced to give major part of their time to the sport, it is tough for the sportspersons to focus on academics. Continuous training and travel with consequent missed classes makes it tough to secure good credits in class attendance and internal assessment which results in adverse performance in semester examinations. The sports centric curriculum and sufficient credit for performance in sports with adequate, flexible teaching schedules, improved training and sports infrastructure in colleges and the universities in India can only raise the standard of cricket and other sports.